Generation of functionally active resident macrophages from adipose tissue by 3D cultures - Arlat, Adèle; Renoud, Marie-Laure; Nakhle, Jean; Thomas, Miguel; Fontaine, Jessica; Arnaud, Emmanuelle; Dray, Cédric; Authier, Hélène; Monsarrat, Paul; Coste, Agnès; Casteilla, Louis; Ousset, Marielle; et al. (Frontiers in Immunology, 2024)
Introduction: Within adipose tissue (AT), different macrophage subsets have been described that played pivotal and specific roles in upholding tissue homeostasis under both physiological and pathological conditions. Nonetheless, studying resident macrophages in vitro poses challenges, as the isolation process and the culture for extended periods can alter their inherent properties. Methods: Stroma-vascular cells isolated from murine subcutaneous adipose tissue were seeded on ultra-low adherent plates in the presence of M-CSF. After four days of culture, the cells spontaneously aggregate to form spheroids. A week later, macrophages begin to spread out of the spheroid and adhere to the culture plate. Results: This innovative 3-dimensional (3D) culture method enables the generation of functional mature macrophages that present distinct genic and phenotypic characteristics compared to bone marrow-derived macrophages. They also show specific metabolic activity and polarization in response to stimulation, but similar phagocytic capacity. Additionally, based on single cell analysis, AT macrophages generated in 3D culture mirror the phenotypic and functional traits of in vivo AT resident macrophages. Discussion: Our study describes a 3D in vitro system for generating and culturing functional AT resident macrophages, without the need for cell sorting. This system thus stands as a valuable resource for exploring the differentiation and function of AT-macrophages in vitro in diverse physiological and pathological contexts.